Análisis del Soft Power como estrategia de política exterior de China hacia Latinoamérica: Caso de estudio la relación bilateral China- Ecuador en el período 2004-2015 - Díaz Segovia, Andrea Sofía. (2019)
This paper analyzes the construction and deployment of China's foreign policy based on soft power with Chinese characteristics as an association strategy with Latin America and Ecuador during the period 2004-2015. The soft power has established itself as an alternative to face the constant changes in the international scenario. The adaptation of soft power with Chinese characteristics has allowed the Asian giant to insert itself into the scenario and define its behavior with a focus on multilateralism, economic diplomacy, responsible and cooperative power policy that seeks to maintain international peace, especially with the Latin America countries. China-Ecuador bilateral relations have been strengthened since 2008 when cooperation in infrastructure for strategic sectors and economic financing became the means of rapprochement between these two actors. Sino-Ecuadorian relations were examined from the perspective of Chinese soft power and it exposed that economic pragmatism is the main element of the Chinese strategy in Ecuador.